Malignant Syndrome Associated with Disseminated Intravascular Coagulation and a High Level of Amylase in Serum, Followed by Diabetic Coma in an Elderly Patient with Parkinsons' Disease during L-dopa Therapy - Saeki, Hideyuki; Kobayashi, Takamasa; Muneta, Shinjiro (Nihon Rōnen Igakkai zasshi, 1998)
A 66-year-old woman with a 7-year history of Parkinsons' disease was admitted to our hospital because of a high fever and disturbance of consciousness. She had been treated with levodopa/benserazide hydrochloride and trihexyphenidyl hydrochloride until admission. On admission, the patient was comatose, her temperature was 40.5°C, her blood pressure was 54/-mmHg, and her pulse rate was 130 beats min. Laboratory tests showed leukocytosis, a high level of creatine kinase in serum and evidence of hyperosmolar non-ketotic diabetic coma (blood glucose, 1, 080mg/dl) and of disseminated intravascular coagulation (DIC). A continuous insulin infusion, antibiotics, nafamostat mesilate, and urinastatin were given, after which the DIC, hyperglycemia, and the level of consciousness were improved. However, levels of creatine kinase, myoglobin, transaminase, and amylase in serum continued to increase, and multiple organ failure was suspected. Furthermore, she became less responsive, diaphoretic, and tremulous; fever and mild rigidity developed. The peak creatine kinase and myoglobin were 11, 095U/l and 12, 520ng/ml, respectively. A diagnosis of malignant syndrome was made, and treatment with levodopa/carbidopa and dantrolene was begun. Within several days, the clinical and laboratory findings improved. We report here a rare case of malignant syndrome associated with DIC followed by diabetic coma in an elderly patient with Parkinsons' disease during L-dopa therapy. Timely diagnosis and treatment of malignant syndrome are important in the management of elderly patients with Parkinsons' disease, because DIC and multiple organ failure may occur in the early stages of malignant syndrome.